Introduction : Borders, Informality, International Trade and Customs - Cantens, Thomas; Ireland, Robert; Raballand, Gael (Taylor and Francis, 2016)
Trading goods is an original human activity that precedes borders (Renfrew, 1969). With the rise of nation-states with demarcated political boundaries, trade that crosses borders became regulated by government institutions such as Customs, with tariffs, quotas, or outright prohibitions. While borders are perhaps not quite “the dead, the fixed, the undialectical, the immobile” (Foucault, 1970, p. 70), they are a formal structure that places less flexibility on trade activities. Focusing on informality thus provided an opportunity to reflect on the governance of international trade, which has been marked by increasing consolidation of its rules in the last decades. Informal cross-border trade affects the symbolic power of the State, particularly where the State takes one of its more concrete forms, as “the borders.” Indeed, at borders, where commodities flows are regulated, informal trade forces governments to balance or choose between rule avoidance with economic contribution, as well as social relations. This tension between the economic, political and social dimensions of informal trade at borders is reflected in this special issue.